2006
DOI: 10.1007/s10549-006-9212-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute bilateral pulmonary emboli occurring while on adjuvant aromatase inhibitor therapy with anastrozole: case report and review of the literature

Abstract: Hormonal therapy is the mainstay of adjuvant treatment for women with early-stage estrogen receptor-positive breast cancer. Recently, the aromatase inhibitors have moved to the forefront of adjuvant hormonal therapy, however, the adverse effects of these agents are not yet fully understood. It is generally accepted that tamoxifen, but not the aromatase inhibitors, is associated with an increased risk of thrombosis in women with breast cancer. Studies comparing aromatase inhibitors to tamoxifen in the adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…This seems to be independent from the presence of cirrhosis as Quintero et al [18] only report on cirrhotic patients and Gostout et al [11] report on a mixed patient group with a predominance of autoimmune diseases. Quintero et al [18] found gastrin levels to be significantly raised in 8 of 11 patients with GAVE and cirrhosis when compared with control patients (0 of 13) and with cirrhosis patients without gastric mucosal changes (2 of 18).…”
Section: Pathophysiologymentioning
confidence: 95%
See 4 more Smart Citations
“…This seems to be independent from the presence of cirrhosis as Quintero et al [18] only report on cirrhotic patients and Gostout et al [11] report on a mixed patient group with a predominance of autoimmune diseases. Quintero et al [18] found gastrin levels to be significantly raised in 8 of 11 patients with GAVE and cirrhosis when compared with control patients (0 of 13) and with cirrhosis patients without gastric mucosal changes (2 of 18).…”
Section: Pathophysiologymentioning
confidence: 95%
“…In non-cirrhotic patients with GAVE autoimmune diseases are most common, with incidences of 62% for autoimmune connective tissue disorders, 31% for Raynaud’s phenomenon and 20% for sclerodactily [11]. Other conditions described in GAVE patients include scleroderma, bone marrow transplantation, chronic renal failure, ischaemic heart disease, hypertension, valvular heart disease, familial Mediterranean fever and acute myeloid leukaemia [11,12,13,14].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations